A BIM-based tool for embodied carbon assessment using a construction classification system - Parece, S. (2024)
Life Cycle Assessment (LCA) is widely accepted for evaluating a building's environmental footprint. Building Information Modelling (BIM) has become the go-to strategy for LCA during design. Still, despite BIM-LCA automating detailed quantity extraction, challenges persist, such as a lack of standardised geometry modelling and information management, as well as a common language between LCA and BIM data. This study proposes a method to assess embodied carbon from BIM models classified using a construction classification system that provides a data structure, maps BIM objects and environmental impacts in LCA databases, and matches different levels of development (LoD) in BIM models. The method was tested on real-world models, resulting in 375 kgCO2e/m2 for the single residential and 426 kgCO2e/m2 for the multi-residential building. These findings revealed its ability to adapt to different LoD and modelling techniques, expedite assessing different design options, and potentially save up to 20 hours of work remodelling.